2019
DOI: 10.31384/jisrmsse/2019.17.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Development Perspective of HRM and Lesson Learned System of Knowledge Management on Project Success Through Project Management Competency Retention

Abstract: This study was conducted to find out the impact of development perspective of Human Resource Management (HRM), and lesson learned system of knowledge management (KM) on project success with the mediation of project management competency retention (PMCR). The data was collected from 310 employees of the telecommunication industry. The results confirmed that the development perspective of HRM and lesson learned through the system of KM has a significant relationship with PMCR and project success. The intervening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Innovation is considered as a source for gaining the competitive advantage for the organizations [ 64 ]. It is also a necessity to improve the performance of the companies, especially for the service sector.…”
Section: Discussionmentioning
confidence: 99%
“…Innovation is considered as a source for gaining the competitive advantage for the organizations [ 64 ]. It is also a necessity to improve the performance of the companies, especially for the service sector.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Müller and Martinsuo (2015) found that lower levels of managerial flexibility in project governance strengthened the effects of high relational norms on project success. Ghafoor et al (2019) found that project governance played a key role in amplifying the impact of benefits management on project success. Furthermore, Zwikael and Smyrk (2015) have suggested that the most effective governance technique in a stable project environment is for the project owner to have control over the project management process.…”
Section: The Moderating Role Of Project Governancementioning
confidence: 99%